Digital Health Interventions for Mental Health, Substance Use, and Co-occurring Disorders in the Criminal Justice Population: A Scoping Review - Leach, Rebecca; Carreiro, Stephanie; Shaffer, Paige M.; Gaba, Ayorkor; Smelson, David (Frontiers in Psychiatry, 2022)
Background: Substance use disorder (SUD), mental health disorders (MHD), and co-occurring mental health and substance use disorders (COD) are common among criminal justice populations. Digital health interventions (DHI) represent an opportunity to expand COD treatment for justice involved populations, but efficacy data are lacking. Objectives: The current scoping review aims to address this gap via following objectives: (1) Describe trends involving DHIs for MHD, SUD, or COD studied in criminal justice settings; and (2) review available evidence for the impact of DHIs on criminal justice-, substance-, and mental health-related outcomes. Methods: PubMed was searched for relevant articles that met the follow inclusion criteria: 1) focus on criminal justice-involved individuals; 2) description of an intervention focused on SUD, MHD, or COD; and 3) use of DHI. Articles were assessed using standardized data abstraction and quality assessment tools. Results: Four-hundred unique articles were identified on initial search, and 19 were included in the final review. The most common focus of the intervention was SUDs. The most common modalities were telehealth and computer assisted interventions, with most utilized as an adjunct to treatment as usual. No DHIs used wearable devices, and one included justice involved youth. Feasibility and acceptability were high, and the studies that measured substance and mental health-related outcomes reported equivocal or positive results. No studies focused on long-term justice-related outcomes. Conclusions: Literature on DHIs for criminal justice involved populations diagnosed with SUD, MHD and COD is limited, and largely focuses on telehealth or eHealth, with less data on mHealth approaches. Future research should focus on the inclusion of diverse populations and include objective monitoring tools.